Treatment of Cd2+ ions using aluminum doped hydroxyapatite (AlHAp) powder - Thom, Nguyen Thi; Mai Thanh, Dinh Thi; Nam, Pham Thi; Phuong, Nguyen Thu; Hong, Cao Thi; Xuyen, Nguyen Thi; Trang, Nguyen Van; Buess-Herman, Claudine (Vietnam Journal of Chemistry, 2017)
Pollution of heavy metals in water is an important problem and is attracting the attention of scientists. It affects the health of humans and destroys the environment, therefore removal of heavy metal ions is necessary. This work is about treatment of Cd2+ ions in the water using aluminum doped hydroxyapatite (AlHAp) powder. The effect of some factors such as contact time, initial Cd2+ concentration, pH solution and mass of AlHAp on adsorption capacity and efficiency was investigated. The experimental adsorption data showed that the Cd2+ removal process follows the pseudo-second-order law. The results about the effect of initial Cd2+ concentration were evaluated using Langmuir and Freundlich adsorption isotherms. Maximum monolayer adsorption capacity was 103 mg/g. Keywords. Aluminum doped hydroxyapatite (AlHAp), Cd2+ ions, adsorption, adsorbent.